The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/bmjopen-2019-034712
|View full text |Cite
|
Sign up to set email alerts
|

Validating the effect of Ondansetron and Mirtazapine In Treating hyperemesis gravidarum (VOMIT): protocol for a randomised placebo-controlled trial

Abstract: IntroductionCurrent pharmacological treatment options for hyperemesis gravidarum have been introduced based on scarce evidence and are often not sufficiently effective. Several case reports suggest that mirtazapine, an antidepressant, may be an effective treatment for hyperemesis gravidarum, but so far there are no controlled trials investigating the potential effect of mirtazapine on hyperemesis gravidarum. The antiemetic ondansetron is currently widely used to treat hyperemesis gravidarum despite sparse evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The use is approved for treatment of major depressive disorder, but might also be effective in anxiety disorders 4,5 . Additionally, mirtazapine has antiemetic effect 6 and might be an effective treatment in hyperemesis gravidarum 7–9 . Thus, knowledge of the safety of mirtazapine use in pregnancy is warranted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use is approved for treatment of major depressive disorder, but might also be effective in anxiety disorders 4,5 . Additionally, mirtazapine has antiemetic effect 6 and might be an effective treatment in hyperemesis gravidarum 7–9 . Thus, knowledge of the safety of mirtazapine use in pregnancy is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Additionally, mirtazapine has antiemetic effect 6 and might be an effective treatment in hyperemesis gravidarum. [7][8][9] Thus, knowledge of the safety of mirtazapine use in pregnancy is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…132 Yet since the publication of these systematic reviews, only one large trial of prednisolone verses placebo has been published and one RCT protocol for mirtazapine verses ondansetron and no others are currently registered with clinicaltrials.gov. 86 96 …”
Section: Discussionmentioning
confidence: 99%
“…Four of these assessed the safety of ondansetron specifically 78 80 81 84. Six were RCTs,35 36 46 49 85 86 ten were retrospective cohort studies and two were prospective cohort studies 37 38. There were also three retrospective case–control studies,87–89 two surveys90 91 and two case reports/series 92 93…”
Section: Question 4: Is Hg Preventable? What Is the Effect Of Prevent...mentioning
confidence: 99%
“…It is of great significance to intervene in the adverse mental state of pregnant women with HG. Ostenfeld et al combined conventional drugs with psychological treatment for HG, effectively promoted the relief of pregnant women's condition [7]. McParlin et al found that psychological treatment can effectively reduce the anxiety and depression of pregnant women with HG and improve the treatment effect [8].…”
Section: Introductionmentioning
confidence: 99%